1990
DOI: 10.1067/mva.1990.16967
|View full text |Cite
|
Sign up to set email alerts
|

Inadequacy of diagnosis related group (DRG) reimbursements for limb salvage lower extremity arterial reconstructions

Abstract: Prospective cost and reimbursement data were collected from 10 centers in various parts of the United States on 566 patients undergoing lower extremity arterial reconstructions for limb salvage and nonlimb salvage indications. Information for each patient was available on indication and type of procedure, length of stay, the type of hospital insurance, and hospital costs/charges. Diagnosis related group payments from each center were used to determine net gain or loss for each patient. Patients were classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The collision of demographics with health policy is problematic because previous studies have shown that treatment of these problems is expensive 3,10,13 and becomes more so with older patients, 3 and the current levels of reimbursement for the treatment of vascular surgical patients, based on global payment schemes such as diagnosis-related groups, are inadequate to cover costs. [13][14][15] The effort to control health care costs has led to a closer scrutiny of all medical interventions. Part of the mandate of health care reform has been to provide care that is not only therapeutically effective but also cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…The collision of demographics with health policy is problematic because previous studies have shown that treatment of these problems is expensive 3,10,13 and becomes more so with older patients, 3 and the current levels of reimbursement for the treatment of vascular surgical patients, based on global payment schemes such as diagnosis-related groups, are inadequate to cover costs. [13][14][15] The effort to control health care costs has led to a closer scrutiny of all medical interventions. Part of the mandate of health care reform has been to provide care that is not only therapeutically effective but also cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…Protracted hospitalization following infrainguinal reconstruction accounts for most health-care dollars spent on these patients. 9 As experience is gained with EISVB, 1-to 2day hospitalizations will be feasible, which will translate into enormous health-care savings. Although cost-effectiveness of EISVB was not assessed in this study, Piano et al 10 looked at their early experience with the EISVB technique and found a modest reduction in LOS compared to conventional open ISVB, which lowered hospital costs from $27,000 to $18,000.…”
Section: Discussionmentioning
confidence: 99%
“…Given that inadequate reimbursement may discourage providers from performing rTHA-I, failure to adequately account for these technically and financially demanding procedures may create barriers to access by patients with PJI. Specifically, the complexity of most rTHA-I procedures, the required resource utilization, and the associated increase in the lengths of hospital stays may delay access to definitive care, as poor reimbursement may lead challenging cases to be deemed undesirable at both the individual surgeon and the institutional level [24][25][26][27][28] . The goal of the present study, therefore, was to investigate temporal reimbursement trends for rTHA-I procedures in relation to those for rTHA-A procedures.…”
mentioning
confidence: 99%